Inpatient Management of Acute Stroke of Unknown Type in Resource-Limited Settings. Issue 3 (March 2022) - Prust, Morgan L.; Saylor, Deanna; Zimba, Stanley; Sarfo, Fred Stephen; Shrestha, Gentle S.; Berkowitz, Aaron; Vora, Nirali
Abstract : Stroke is the second leading cause of death and disability worldwide, with a disproportionate burden on low- and middle-income countries. Critical elements of guideline-based stroke care developed in high-income countries are not applicable to resource-limited settings, where lack of access to neuroimaging prevents clinicians from distinguishing between ischemic stroke and intracranial hemorrhage, requiring challenging clinical decision-making, particularly in the acute setting. We discuss strategies for acute inpatient management of stroke of unknown type with a focus on blood pressure management and antiplatelet therapy when neuroimaging is unavailable, and review some of the challenges and strategies for successfully implementing stroke unit care in resource-limited health care settings.